Biochemistry properties of Platinum nanoparticles and Adatoms (Journal of Pharmaceutical Negative Results, 2023)
Dielectric constants, dielectric degradation and A.C. conductivity have been calculated according to the doping material frequency and composition. High AC-conductivity and low dielectric constant were observed at higher frequencies. The above hypothesis can be clarified by 'Maxwell Wagner Model' and may offer new insights into the manufacture of dialectically conceivable nanomaterials. The degradation of Rhoda mine B in the UV visible light has been investigated for the photocatalytic function of our samples. The analysis of photocatalyst provides a convenient way to determine your destiny by various reutilizations.